Automatic monitoring of photovoltaic cells performance on solar aircraft - Sahwee Z.; Hussain H.; Kadir M.K.A.; Razali M.F.; Zainol M.Z.; Sarmin S.A. (2023)
The development towards the usage of green energy sources is currently a major concern in today's lifestyle due to the limited supply of fossil-based energy. Many have turned to alternative energy resources that are less polluting to the environment. Replacement of the vehicle's fuel-based engine to an electric-based engine by using alternative or hybrid energy is one of the possible paths that many studies are conducted. In the aviation field, harvesting solar energy by using solar panel to charge aircraft on-board batteries could reduce the dependency on fuel. As with any other energy conversion technology, the solar panel performance needs to be monitored so that the power output can always be maintained at maximum available power. This paper presents a research and development of a system to monitor the health of photovoltaic panel installed on aircraft by measuring its voltage and current. The measurement is conducted using low power microcontroller. The system is capable to automatically measure the output of every solar panel installed in the system by connecting them with a matched load during the measurement process. The power output is then compared to the initial values prior to installation to determine how much power is currently being generated. By knowing the actual power output of each solar panel, less efficient or defective panel can be identified and replaced during maintenance. The system can be implemented not only for an aircraft but also applicable to other system that uses solar panel as their energy resources. (2012) Trans Tech Publications, Switzerland.